Rewrite the equation as <math><mstyle displaystyle="true"><mfrac><mrow><mn>9</mn></mrow><mrow><mn>5</mn></mrow></mfrac><mi>c</mi><mo>+</mo><mn>32</mn><mo>=</mo><mi>f</mi></mstyle></math> .

Combine <math><mstyle displaystyle="true"><mfrac><mrow><mn>9</mn></mrow><mrow><mn>5</mn></mrow></mfrac></mstyle></math> and <math><mstyle displaystyle="true"><mi>c</mi></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mn>32</mn></mstyle></math> from both sides of the equation.

Multiply both sides of the equation by <math><mstyle displaystyle="true"><mfrac><mrow><mn>5</mn></mrow><mrow><mn>9</mn></mrow></mfrac></mstyle></math> .

Simplify <math><mstyle displaystyle="true"><mfrac><mrow><mn>5</mn></mrow><mrow><mn>9</mn></mrow></mfrac><mo>⋅</mo><mfrac><mrow><mn>9</mn><mi>c</mi></mrow><mrow><mn>5</mn></mrow></mfrac></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Cancel the common factor of <math><mstyle displaystyle="true"><mn>9</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>9</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>9</mn><mi>c</mi></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Simplify <math><mstyle displaystyle="true"><mfrac><mrow><mn>5</mn></mrow><mrow><mn>9</mn></mrow></mfrac><mo>⋅</mo><mrow><mo>(</mo><mi>f</mi><mo>-</mo><mn>32</mn><mo>)</mo></mrow></mstyle></math> .

Apply the distributive property.

Combine <math><mstyle displaystyle="true"><mfrac><mrow><mn>5</mn></mrow><mrow><mn>9</mn></mrow></mfrac></mstyle></math> and <math><mstyle displaystyle="true"><mi>f</mi></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mfrac><mrow><mn>5</mn></mrow><mrow><mn>9</mn></mrow></mfrac><mo>⋅</mo><mo>-</mo><mn>32</mn></mstyle></math> .

Combine <math><mstyle displaystyle="true"><mfrac><mrow><mn>5</mn></mrow><mrow><mn>9</mn></mrow></mfrac></mstyle></math> and <math><mstyle displaystyle="true"><mo>-</mo><mn>32</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>32</mn></mstyle></math> .

Move the negative in front of the fraction.

Do you know how to Solve for c f=9/5c+32? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.